Developing Interpreting Competence Scales in China - Wang, Weiwei; Xu, Yi; Wang, Binhua; Mu, Lei (Frontiers in Psychology, 2020)
Tertiary-level interpreter training and education have developed rapidly in China, and more than 500 undergraduate and postgraduate degree programs have been launched over the past decade. Despite the rapid development, there has been no standardized framework allowing for the reliable and valid measurement of interpreting competence in China. Against this background, the China Standards of English (CSE), which are the Chinese counterpart to the Common European Framework of Reference (CEFR), were unveiled in 2018 after four years of government-funded research and validation. One vital component of the CSE is the descriptor-referenced interpreting competence scales. This article provides a systematic account of the design, development, and validation of the interpreting competence scales in China. Within the CSE, the construct of interpreting competence was defined according to an interactionist approach. It encompasses not only cognitive abilities, interpreting strategies, and subject matter knowledge, but also considers performance in typical communicative settings. Based on the construct definition, a corpus of relevant descriptors was built from three main sources, including: a) interpreting training syllabuses, curricular frameworks, rating scales, and professional codes of conduct; b) previous literature on interpreting performance assessment, competence development, and interpreter training and education; c) exemplar-generation data on assessing interpreting competence and typical interpreting activities, which were collected from interpreting professionals, trainers, and trainees. The corpus contains 9,208 descriptors of interpreting competence. A mixed-method survey was then conducted to analyze, scale, and validate the descriptors among 30,682 students, 5,787 teachers, and 139 interpreting professionals from 28 provinces, municipalities, and regions in China. The finalized set included 369 descriptors that reference interpreting competence. The CSE-Interpreting Competence Scales with theoretically and empirically based descriptors represent a major effort in research on interpreting competence and its assessment, and they have significant potential to be applied widely in interpreting training, research, and assessment.